Breaking Isolation: Social Work in Solidarity with Migrant Workers through and beyond COVID-19. Issue 1 (3rd November 2021) - Alcaraz, Nellie; Lorenzetti, Liza; Thomas, Sarah; Dhungel, Rita
Abstract: In the early months of COVID-19's proliferation through Canadian communities, the now largely documented uneven impacts and burdens of the illness were emerging. Among the early COVID-19 casualties were workers in Alberta's meatpacking plants, with infection rates so high that the news quickly gained international attention. The Cargill meatpacking plant, overwhelmingly staffed by temporary foreign workers with no permanent status or citizenship rights, was the site of the largest single coronavirus outbreak in Canada. The need for a community response to this emerging crisis was a focal discussion for a newly formed network of social workers. A multileveled series of actions and systems advocacy were put in place. These actions would foment a vibrant and diverse "community of communities" while also unveiling challenges and obstacles to the work during a period of a shifting health landscape, shutdowns, and changing legislation. This article focuses on the development of a grassroots and transformative community-led response to COVID-19, describing strategies, implementation, and challenges in the "real life" context of the recent pandemic. Key learnings for postpandemic community organizing and social work solidarity actions are highlighted.